Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Solve the system. Algebra 2?

Solve the system.

9 = 4x - 2

2x + 6 = y

Update:

Solve the system.

9 = 4x - 2

2x + 6 = y

A.(2, 10)

B.no solution

C.infinite solutions

D.(-2, 2)

Update 2:

= 4x - 2y

2x + 6 = y

A.(2, 10)

B.no solution

C.infinite solutions

D.(-2, 2)

Update 3:

9 = 4x - 2y

2x + 6 = y

A.(2, 10)

B.no solution

C.infinite solutions

D.(-2, 2)

Yahoo Answers is glitching.

4 Answers

Relevance
  • Ray S
    Lv 7
    6 years ago

    ➊ 9 = 4x - 2y

    ➋ 2x + 6 = y                   ← Multiply this equation by 2 to get a 2y

    ➊ 9 = 4x - 2y

    ➋ 4x + 12 = 2y                ← Now, substitute 4x+12 in for 2y in equation ➊

    ➊ 9 = 4x - (4x+12)           ← Now, solve for x

        9 = 4x - 4x 12

        9 = 12                         ← This is false for ALL values of x.

                                              That tells you there is no solution to this system

                                              Note:

                                              If you write the two original equations in the form y=mx+b,

                                              you'll find that these lines have the same slope but different y-intercepts.

                                              They are distinct parallel lines which never intersect ... So, no solution

        ANSWER

      B.no solution

    Have a good one!

    .

  • Anonymous
    6 years ago

    Solve the system.

    9 = 4x - 2

    2x + 6 = y

    Are you sure you have the correct system ??

    4x = 11

    x = (11/4)

    y = (11/2) + (12/2) = (23/2)

    (11/4, 23/2)

    check your problem !!

    the two lines are PARALLEL...there is NO SOLUTION

  • 6 years ago

    9 = 4x - 2y --- (1)

    2x + 6 = y --- (2)

    Substituting (2) into (1), we will get:

    9 = 4x - 2(2x + 6)

    9 = 4x - 4x - 12

    9 = -12

    Hence, there is no solution.

  • 6 years ago

    2y try that man.

Still have questions? Get your answers by asking now.